French vocabulary - Kendris, Christopher (Barron's, 2012)
Here is a practical carry-along books for French language students and travelers to French-speaking countries. Purchasers of all titles in Barron's Vocabulary Series have expressed special satisfaction with these small-format books because they go beyond the standard vocabulary needs of students taking language courses, and include helpful words and phrases for reading foreign language newspapers and magazines. Words are grouped in useful categories for quick reference, and listed alphabetically within each category